Employment outlook in banking occupations. Banking functions. Training and qualifications. Earnings and working conditions. Employment trends and outlook (United States Department of Labor, 1953)
Bureau of Labor Statistics. Occupational Outlook Series. Bulletin, 1156. In cooperation with Veterans Administration.